Research on the evaporation pressure calculation model of LNG tank container - Zhidong Yu; Bao Li (PLoS ONE, 2025)
The changes in pressure, temperature, and filling rate inside LNG tank container are related to non-destructive storage time. In order to solve these problems, it was necessary to understand the distribution of temperature, pressure and evaporation in the LNG storage tank during transportation. The study on the relationship between the initial filling rate and safe storage time is still rare. Based on the principle of mass conservation and energy conservation, the pressure calculation model of the horizontal low-temperature LNG tank was established and verified by an experiment. A study was conducted on the LNG tank container in Golmud-Lhasa, and experimental data such as pressure changes in LNG tank containers during transportation were obtained. The storage calculation results obtained by the model were compared with the experimental data. The research results show that the simulated calculated values agree well with the experimental values, there was an “optimal initial filling rate” in the LNG tank. When the initial filling rate was less than the optimal initial filling rate, the safe storage time of the tank increases with the increase of the initial filling rate. When the initial filling rate was greater than the optimal initial filling rate, the safe storage time of the tank decreases with the increase of the initial filling rate.